Innovation and Entrepreneurship, 3rd Edition - R. Bessant, John (2023)
This book has been developed specifi cally for students of Business and Management Studies, and for Science and Engineering students studying courses on innovation and/or entrepreneurship. It is designed to complement our best-selling text Managing Innovation: Integrating Technological, Market and Organizational Change (5th edn, John Wiley & Sons Ltd, 2013), which is focused more on the needs of specialist postgraduate and post-experience audiences.